PERSEPSI MAHASISWA EKONOMI SYARIAH TERKAIT TA'DZIR PADA BANK SYARIAH - Mush'ab, Muhammad; Mubarok, Jaih; Susanto, Hari (Universitas Ibn Khaldun Bogor, 2024)
Islamic financial literacy still shows a very minimal number, namely 8.93% according to publications from the Financial Services Authority in 2019 which means that when there are 100 Indonesians, 8 of them have a fairly good literacy towards Islamic finance. So this is the reason why the market share of Islamic banks is low in Indonesia because literacy in Islamic finance is also low. Students as agents of call to advance Islamic finance, it is necessary to have a fairly good literacy, moreover there are many thoughts that are the antithesis of Islamic economic thought that is fatwaed by the DSN-MUI. The institution is an institution recognized by the government in issuing sharia economic fatwas in Indonesia. Therefore, Islamic economics students must have the same perception as what the DSN-MUI fatwa has made. Late fines become a contract that gets a negative stigma in the community because there are thoughts that are contrary to the DSN-MUI fatwa. Therefore, it is important for Islamic economics students to fortify themselves with good literacy in order to have a good perception. STIS Al-Wafa provides good literacy to its students, especially those who have passed semester 5 because they have obtained literacy related to contemporary muamalah fiqh. So that most of them have a good perception of late fees in Islamic banks. Then also as a student, it is also necessary to deepen material about benefits because it can help in understanding a fatwa product that is relevant to its era.